The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.enpol.2020.111243
|View full text |Cite
|
Sign up to set email alerts
|

Smart choices? An experimental study of smart meters and time-of-use tariffs in Ireland

Abstract: The introduction of smart technology and dynamic tariffs (such as time-of-use tariffs) provides multiple potential benefits for electricity markets. However, time-of-use tariffs represent an additional complexity for consumer tariff choices in electricity markets. How well consumers may choose between different types of tariffs, and whether certain tools can improve these choices, are therefore important questions for energy regulators and policy makers. This paper presents the results of an exploratory study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…Table 2 compares the sample and population of Florianopolis region profiles. The sample is younger than the actual population, which is common to other online surveys (e.g., Gerpott and Paukert, 2013, Chou and Yutami, 2014, Chou et al, 2015, Belton and Lunn, 2020. Specifically, it is composed of a larger number of 17 to 34 years old (about 20% more) and a lower number of 55+ year old (about half) relative to the target population.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Table 2 compares the sample and population of Florianopolis region profiles. The sample is younger than the actual population, which is common to other online surveys (e.g., Gerpott and Paukert, 2013, Chou and Yutami, 2014, Chou et al, 2015, Belton and Lunn, 2020. Specifically, it is composed of a larger number of 17 to 34 years old (about 20% more) and a lower number of 55+ year old (about half) relative to the target population.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…This result is important, because clocks like those we tested have been designed and promoted in markets where ToU tariffs are already available. Previous research has also indicated that consumers have difficulty processing tariffs presented as clocks (Belton and Lunn, 2020). The implication of this research is that primers for consumers should avoid this type of presentation and instead use simple tables.…”
Section: Discussionmentioning
confidence: 87%
“…Comprehension and recall improved with the linear representation (BE Works, 2019). A more recent study conducted in Ireland revealed that such linearised representation was actually associated with worse understanding and recall of features of ToU tariffs, compared to a simple table (Belton and Lunn, 2020).…”
Section: Communicating Energy-related Information To Enhance Comprehensionmentioning
confidence: 99%
“…The proposed formulation also ensures recovery of regulated costs, but do not guarantee profit maximization of customers; instead, the tariff system incentivizes peak shaving that leads to economic efficiency. However, the complexity of the optimization proposals is a limitation while considering the impact of customer understandability on the performance of a tariff system [5][6][7]. A more accurate (but simple) representation of welfare maximization is left for future work.…”
Section: Formulation Of the Tariff Systemmentioning
confidence: 99%
“…This need for simplicity has captured particular attention in the literature. In [5], an experiment is conducted in Ireland to test consumer behaviour towards smart meters and time-of-use tariffs. The results suggest that consumers struggle to match their electricity usage to appropriate tariffs, and that a general aversion to more complex tariffs can lead to sub-optimal choices.…”
Section: Introductionmentioning
confidence: 99%